Harry Harlow's pit of despair: Depression in monkeys and men. Issue 2 (18th January 2022) - van Rosmalen, Lenny; Luijk, Maartje P. C. M.; van der Horst, Frank C. P.
Abstract: Major depressive disorder is the most common mood disorder in the United States today and the need for adequate treatment has been universally desired for over a century. Harry Harlow, famous for his research with rhesus monkeys, was heavily criticized when he undertook his controversial experiments trying to find a solution for depression in the 1960s–1970s. His research, however, did not just evolve gradually from his earlier research into learning and into love. Recently disclosed hand‐written notes show, for the first time, the severity of Harlow's depressions as he wrote in detail about his feelings and thoughts during his stay in a mental hospital in 1968. In these notes, Harlow repeatedly vowed to put every effort into finding a cure for depression. This may, for a large part, explain why he did not stop his rigorous animal experiments where critics argue he should have, and he eventually managed to book positive results.